MiR‐200a/b/‐429 downregulation is a candidate biomarker of tumor radioresistance and independent of hypoxia in locally advanced cervical cancer. Issue 6 (15th February 2022) - Nilsen, Anja; Hillestad, Tiril; Skingen, Vilde E.; Aarnes, Eva‐Katrine; Fjeldbo, Christina S.; Hompland, Tord; Evensen, Tina Sandø; Stokke, Trond; Kristensen, Gunnar B.; Grallert, Beata; Lyng, Heidi
Abstract : Many patients with locally advanced cervical cancer experience recurrence within the radiation field after chemoradiotherapy. Biomarkers of tumor radioresistance are required to identify patients in need of intensified treatment. Here, the biomarker potential of miR‐200 family members was investigated in this disease. Also, involvement of tumor hypoxia in the radioresistance mechanism was determined, using a previously defined 6‐gene hypoxia classifier. miR‐200 expression was measured in pretreatment tumor biopsies of an explorative cohort ( n  = 90) and validation cohort 1 ( n  = 110) by RNA sequencing. Publicly available miR‐200 data of 79 patients were included for the validation of prognostic significance. A score based on expression of the miR‐200a/b/‐429 (miR‐200a, miR‐200b, and miR‐429) cluster showed prognostic significance in all cohorts. The score was significant in multivariate analysis of central pelvic recurrence. No association with distant recurrence or hypoxia status was found. Potential miRNA target genes were identified from gene expression profiles and showed enrichment of genes in extracellular matrix organization and cell adhesion. miR‐200a/b/‐429 overexpression had a pronounced radiosensitizing effect in tumor xenografts, whereas the effect was minor in vitro . In conclusion, miR‐200a/b/‐429 downregulation is a candidate biomarker of central pelvic recurrence and seems to predict cell adhesion‐mediated tumor radioresistance independent of clinical markers and hypoxia. Abstract : Diagnostic biomarkers for identifying tumor radioresistance in patients with cervical cancer are highly needed. Here, we report a new candidate biomarker based on the miR‐200a/b/‐429 cluster expression in tumor biopsies. Low expression of miR‐200a/b/‐429 in patients was found to predict the risk of central pelvic recurrence after chemoradiotherapy. Additionally, miR‐200a/b/‐429 overexpression radiosensitized tumor xenografts. Moreover, the expression of the miR‐200a/b/‐429 was independent of known risk factors and was predictive of cell adhesion‐mediated radioresistance in patients.